Palynological evidence for Holocene climatic and oceanographic changes off western South Africa. (1st June 2017) - Zhao, Xueqin; Dupont, Lydie; Schefuß, Enno; Bouimetarhan, Ilham; Wefer, Gerold
Abstract: Atmospheric and oceanographic interactions between the Atlantic and Indian Oceans influence upwelling in the southern Benguela upwelling system. In order to obtain a better knowledge of paleoceanographic and paleoenvironmental changes in the southern Benguela region during the Holocene, 12 marine surface sediment samples and one gravity core GeoB8331-4 from the Namaqualand mudbelt off the west coast of South Africa have been studied for organic-walled dinoflagellate cysts in high temporal resolution. The results are compared with pollen and geochemical records from the same samples. Our study emphasizes significantly distinct histories in upwelling intensity as well as the influence of fluvial input during the Holocene. Three main phases were identified for the Holocene. High percentages of cysts produced by autotrophic taxa like Operculodinium centrocarpum and Spiniferites spp. indicate warmer and stratified conditions during the early Holocene (9900-8400 cal. yr BP), suggesting reduced upwelling likely due to a northward shift of the southern westerlies. In contrast, the middle Holocene (8400-3100 cal. yr BP) is characterized by a strong increase in heterotrophic taxa in particular Lejeunecysta paratenella and Echinidinium spp. at the expense of autotrophic taxa. This indicates cool and nutrient-rich waters with active upwelling probably caused by a southward shift of the southern westerlies. During the late Holocene (3100 cal. yr BP to modern), Brigantedinium spp. and other abundant taxa interpreted to indicate fluvial nutrient input such as cyst of Protoperidinium americanum and Lejeunecysta oliva imply strong river discharge with high nutrient supply between 3100 and 640 cal. yr BP. Highlights: Modern dinoflagellate cyst distribution in the southern Benguela region was assessed. Holocene dinoflagellate cyst records from marine sediment core were investigated. A multiproxy approach was applied using pollen and geochemical records. Distinct oceanic conditions were determined associated with climate changes on land. Influence of Agulhas leakage to the study site was absent during the Holocene.